Component-based development for enterprise systems : applying the SELECT Perspective - Allen, Paul, 1949- (Managing object technology series ;, 1998)
This book distills the experience of the authors in dealing with problems in industry that can be solved by using The Select Perspective. A pragmatic component-based approach for the development of enterprise systems, The Select Perspective comprises a unique blend of techniques, architecture, and process. The approach in this book offers a streamlined set of modeling techniques based on Unified Modeling Language (UML); uses a service-based architecture that provides an overall design philosophy for reusable software that addresses the needs of the business, not the technology; and provides a clearly defined software process that offers guidance on how to employ the knowledge base of available techniques.